Functional trait composition and diversity patterns of marine macrobenthos across the Arctic Bering Sea. (July 2019) - Liu, Kun; Lin, Heshan; He, Xuebao; Huang, Yaqin; Li, Zhong; Lin, Junhui; Mou, Jianfeng; Zhang, Shuyi; Lin, Longshan; Wang, Jianjun; Sun, Jun
Highlights: The macrobenthic functional traits of the Bering Sea were studied for the first time. Biological traits composition showed clear spatial variations across the study area. Benthic ecosystem of Bering Sea is susceptible to species loss or structural shifts. Abstract: The use of functional trait analysis has been advocated to uncover the global mechanisms behind biodiversity responses to environmental variation, but the application of this approach to the Arctic macrobenthic community is underdeveloped relative to that used for other organism groups. Based on several summer surveys (July to September 2010, 2012, 2014 and 2016) in the Bering Sea, we used biological trait analysis (BTA) to quantify the composition and diversity of macrobenthic biological traits along an environmental gradient ranging from the shallowest portion of the continental shelf to the shelf break and deep basin. Our results show a clear shift in the macrobenthic functional composition through the application of abundance- and biomass-based measurements in six different subregions of the Bering Sea. The macrobenthic community of the south-western shelf and shelf break of the Bering Sea, an area with silty-sand sediment, was mainly composed of taxa characterized by high body flexibility, vermiform, and tube-dweller/burrower modalities or large, semi-motile, deposit feeder and flattened dorsally modalities. However, the community of the north-eastern shelf of the Bering Sea with sandy sediment was mainly characterized by organisms characterized as motile surface crawlers and carnivores/scavengers. Similar to the factors that determine the taxonomic distribution and composition of the macrobenthos, sediment composition and depth were found to be the main factors that affect the distribution of the macrobenthic functional structure in the study area. The species and functional diversity of the macrobenthos show a strong linear relationship, potentially indicating that the community exhibits relatively low functional redundancy and that the benthic ecosystem is vulnerable to species loss or regime shifts.